THE EFFECT OF DIFFERENT ROTATIONAL SPEED (RPM) DISC MILL TOWARD THE UNIFORMITY INDEX OF BROWN SUGAR - Kharisma, Novi (The University of Lampung, 2014)
The aims of this researchwere to find out the effect of different rotational speed of discmill to the size spreadingand uniformity index of brown sugar and to knowthe optimal rotational speed of disc mill producing size of 0,8to 1,2mm. The parameters observed were water content, fineness modulus (FM), uniformity index, grain yield,bulk density, and color. The research was conducted at five variations of rotational speed which were 800, 900,1000, 1100, and 1200 rpm with 1500 g sample for each variations.The results show that the water content ofbrown sugar is between 1,30 and 1,76%, the fineness modulus is around 1,99 to 4,74, the particle size is around0,41 to 2,79mm, the highest grainyield reaches 45,32%atactual speed of 900 rpm, and the range of bulk densityis about 721,07 to 740,40 kg/m3. The color of the middle fraction compared with commercial sugar is notsignificantly different. The color indexes of middle fraction in each treatment are IRED 0,41 to 0,43, IGREEN around0,35, and IBLUE 0,22 to 0,24. Based on the analysis of variance and Duncan’s method (α < 0,05) show that therotational speed (rpm) significantly affects to the particle size, fineness modulus, and grain yield, but not to thewater content, bulk density and color.